2022
DOI: 10.1155/2022/9249627
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Strategy for the Treatment of Allergic Rhinitis: Regulating Treg/Th17 and Th1/Th2 Balance In Vivo by Vitamin D

Abstract: Objective. This prospective study is aimed at observing the number of nasal itching and sneezing in rats from the macroscopic level and examine the pathological changes of nasal mucosa, Th1 and Th2-related cytokines, and Treg/Th17 by vitamin D3 administration from the microscopic level, in order to explore the role of vitamin D in allergic rhinitis and to provide theoretical guidance for prevention and treatment. Results. There were significant differences in nasal itching and sneezing between the administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A study has shown that vitamin D 3 supplements can reduce the severity of atopic dermatitis and AR in children (20). Through animal experiments, some scholars have revealed that vitamin D 3 has a preventive and therapeutic effect on AR, which provides theoretical guidance for practical application (21). Comprehensive metabolomic analysis has demonstrated the links between vitamin D-related metabolites and the gut microbiome as well as immunosensitivity responses associated with childhood allergy (22).…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that vitamin D 3 supplements can reduce the severity of atopic dermatitis and AR in children (20). Through animal experiments, some scholars have revealed that vitamin D 3 has a preventive and therapeutic effect on AR, which provides theoretical guidance for practical application (21). Comprehensive metabolomic analysis has demonstrated the links between vitamin D-related metabolites and the gut microbiome as well as immunosensitivity responses associated with childhood allergy (22).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of IL-6, TNF-α, IL-23, IL-17, and IL-10 were negatively correlated with the serum 25(OH)D level. Research studies show that after vitamin D treatment, Treg and Th2 cells increased, and Th17 and Th1 cells decreased inconsistently ( 30 , 31 ). IL-6 inhibits the expression of Foxp3 during Treg differentiation ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although insufficiency and/or deficiency of vitamin D have been reported in children with SLE (11,12), there is relatively few studies on vitamin D levels in pediatric SLE. There are various reasons for the decrease of serum vitamin D levels in patients (30,31). IL-6 inhibits the expression of Foxp3 during Treg differentiation (32).…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%